Simulation of economic losses from tropical cyclones in the years 2015 and 2050: the effects of anthropogenic climate change and growing wealth - Silvio Schmidt; Claudia Kemfert; Eberhard Faust (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper simulates the increase in the average annual loss from tropical cyclones in the North Atlantic for the years 2015 and 2050. The simulation is based on assumptions concerning wealth trends in the regions affected by the storms, considered by the change in material assets (capital stock). Further assumptions are made about the trend in storm intensity resulting from anthropogenic climate change. The simulations use a stochastic model that models the annual storm loss from the number of storms and the loss per storm event. The paper demonstrates that increasing wealth will continue to be the principle loss driver in the future (average annual loss in 2015 +32%, in 2050 +308%). But climate change will also lead to higher losses (average annual loss in 2015 +4%, in 2050 +11%). In order to reduce the uncertainties surrounding the assumptions on the trend in capital stock and storm intensity, a sensitivity analysis was carried out, based on the assumptions from current studies on the future costs for tropical storms.
Keywords: 330; Climate change; tropical cyclones; natural catastrophes; insurance; Klimaveränderung; Sturm; Soziale Kosten; Versicherungsschaden; Prognose; Simulation; Wahrscheinlichkeitsrechnung; USA